Analysis of the Effectiveness of Mango Leaves (Mangifera indica) as a Phytoimunostimulant on Common Carp (Cyprinus carpio) in Brackish Water - Saputra, Andika; Effendi, Irwan; Mardalisa, Mardalisa (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2023)
The problems that are often experienced when cultivating goldfish are diseases caused by pathogens that attack cultivated fish. The cause of disease in fish is caused by interactions between fish, pathogens and their habitat environment that can cause death in fish. The solution to this problem is to provide a phytoimmunostimulant derived from mango leaves (Mangifera indica). The purpose of this study was to determine the effect of mango leaves on the hematology and physiology of common carp. This research was conducted in January-April 2022. The method used in this research is an experimental method by comparing data. Parameters observed were total erythrocytes, hemoglobin, hematocrit, blood glucose, absolute body weight growth, survival rate, and water quality. Based on the research that has been done, it can be concluded that the addition of 1.5% mango leaf powder into fish feed as a phytoimmunostimulant affects the hematological and physiological effects of common carp. Common carp treated with phytoimmunostimulants in fresh water had higher mean values ​​(total erythrocytes 1.75x106 cells/mm3, hematocrit 33.66%, and hemoglobin 8.13 g/dL) compared to data in brackish water (total erythrocytes 1.54x106 cells/mm3, hematocrit 30.66%, and hemoglobin 7.76 g/dL).